Understanding Uncertainty of Software Requirements Engineering: A Systematic Literature Review Protocol - M. Salih, Ahmad; Omar, Mazni; Yasin, Azman (Springer, 2018)
Requirements engineering uncertainty is considered as one of the main problems in software industry. It can complicate early decisions on requirements and architecture and might expose the software project to significant risks. Continuous effort by researchers has resulted in a largely grown body of work on uncertainty in software requirements. In this paper, a systematic literature review protocol is presented to investigate the research literature on approaches deals with uncertainty in software requirements engineering. Requirements management was widely studied on the uncertainty in software requirement engineering. Results showed that review and analyses approach are most widely approaches dealt with requirements uncertainty and some were briefly explained. Further research is required on the identification of prominent causes of software requirements uncertainty and the solution to cope with such causes.